Pareto-Improving Reforms of Tax Deductions - Sebastian Köhne; Dominik Sachs (Center for Economic Studies and ifo Institute (CESifo), 2019)
We analyze Pareto-efficient tax deduction rules for work-related expenses. Pareto efficiency dictates a strict rule for marginal deductions along the income distribution. An immediate implication is a recipe for designing Pareto-improving reforms. We apply our theory and simulate a Pareto-improving reform that introduces deductions for non-care household services (housekeeping, gardening, laundry) in the United States. The reform combines marginal deduction rates for household services between 55% and 85% with a slight increase in marginal tax rates.
Keywords: D82; H21; 330; optimal taxation; tax deduction; Pareto-improving tax reform